(untitled) (Contemporary Journal of Social Science Review, 2025)
SUD Substance use disorder (SUD) is a chronic illness that is typified by compulsive use of a substance, high level of cravings, and high probability of relapse. Mindfulness-based interventions (MBIs) have become an exciting addition to adjunctive therapy that are likely to encourage awareness, emotional regulation, and cognitive control that can decrease cravings and stop relapses. The current research focused on the efficacy of an eight-week strategy on mindfulness-based reduction of craving and risk of relapse in 50 patients undergoing treatment in a rehab center. The participants were separated into an intervention (n = 25) and a control group (n = 25). Pre- and post-intervention measurement involved the use of standardized tools, such as Drug Craving Questionnaire (DCQ), Relapse Risk Scale (RRS) and Five Facet Mindfulness Questionnaire (FFMQ). The findings showed that the intervention group had significant decreases in the intensity of cravings and risk of relapse with higher mindfulness scores than the control group. Correlational analyses demonstrated negative relations among mindfulness and craving and relapse whereas regression analysis demonstrated that mindfulness substantively forecasted reduced risk of relapse. The results indicate that MBIs can positively contribute to the improvement of their self-regulation and minimization of the vulnerabilities associated with addiction. The research highlights the relevance of the inclusion of mindfulness techniques in rehabilitation interventions to enhance recovery in the long run.